Interest In Transacting : The Role Of Lifestyle And The Effectiveness Of Advertising On Instagram Social Media - Harjadi, Dikdik; Fitriani, Lili Karmela (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
The purpose of this study is to ascertain how lifestyle affects interest in transactions on social media platforms like Instagram and how effective advertising is in generating interest in transactions on these platforms in Kuningan District. The descriptive verification research method is the one that was employed. Multiple linear regression analysis is the technical analysis that is used. The study's findings indicate that: Interest in transacting on social media platforms like Instagram is positively and significantly influenced by one's lifestyle. The interest in transacting on social media platforms like Instagram is positively and significantly impacted by the efficacy of advertising